MENGHINDARI KONFLIK AKIBAT PENYIARAN HASIL HITUNG CEPAT (QUICK COUNT) PEMILIHAN PRESIDEN 2019 (Kajian Penerapan Nilai Humanis dan Religius) - Susanto susanto (PIKTORIAL : Journal of Humanities, 2019)
ABSTRACT This study aims to find out how to avoid conflict due to the broadcast of the quick count results of the presidential election in terms of humanist and religious values. While the benefits of this research are for the community in general to enrich understanding of how to avoid social conflict. This study the authors use library research data collection or library research. The author utilizes library resources to obtain research data by searching and searching documents and books relating to the problem under study so that it becomes research material. In this study using descriptive research methods by grouping qualitative data. In this study, results were obtained that in order to avoid conflicts due to broadcasting the results of the quick count of the 2019 presidential election, attitudes that reflect humanist and religious values were needed. Humanist values are reflected in the attitudes and behavior that fast-counting broadcasting is just a development of science while the results of the real calculation are from the General Election Commission. Quick count broadcasting is not used as a basis for a claim for victory that allows other parties to be hurt. Viewed from the religious side, which needs to be interpreted, the process and implementation of elections run smoothly and become a part that must be grateful for by humans as religious people who have religious souls. Keywords: Conflict, Quick Count, General Election, Humanist and Religious